The Relationship of Illegal Fishing with the Entry of Illegal Immigrants as a Form of Transnational Crime - Lewerissa, Yanti Amelia (Law Research Review Quarterly, 2018)
This writing aims to assess the relationship between illegal fishing and the entry of illegal immigrants as a form of transnational crime. The research method used is normative legal research. Sources of legal materials used are primary, secondary and tertiary legal materials related to writing. Data collection techniques through literature study and analyzed qualitatively. From the results of the study showed that Indonesia as the largest archipelago in the world with 17,504 large and small islands and a coastline length of 81,700 km 2 makes Indonesia a country that has abundant marine resource potential. For this reason, many foreign naval fleets make Indonesian waters the main destination for their capture fisheries. These foreign-owned capture fisheries companies, the exploitation of marine resources that we have owned both legally and illegally. Likewise what happened in the Maluku region. As an archipelago province with an area of ​​658,295 km 2 with a coastline length of 11,000 km 2, the Maluku sea holds the potential for abundant marine wealth. Arafura Sea is one of the fisheries management areas which is often the main destination of foreign-owned fishing fisheries. Illegal fishing activities not only make Indonesia economically disadvantaged, but there is another problem, namely the existence of other crimes that usually follow the illegal fishing activities. One of them is the entry of illegal immigrants into Indonesian territory. It was concluded that there was a connection between illegal fishing and the entry of illegal immigrants into Indonesia.